2020
DOI: 10.1017/dmp.2020.156
|View full text |Cite
|
Sign up to set email alerts
|

Are Iranian Sulfur Mustard Gas-Exposed Survivors More Vulnerable to SARS-CoV-2? Some Similarity in Their Pathogenesis

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that emerged as a health problem worldwide. It seems that COVID-19 is more lethal for Iranian veterans with a history of exposure to mustard gas. There are some similarities in the pathogenesis of SARS-CoV-2 and mustard gas in immune system disruption and pulmonary infection. SARS-CoV-2 and mustard gas inducing oxidative stress, immune system dysregulation, cytokine storm, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…All evidence suggests a possible destructive role for IL-6 in patients with SARS-COV-2 infection [71]. Shock and organ failure in several organs, such as the kidneys, heart, lungs, and liver, are severely damaged by cytokine storms caused by an increase in inflammatory cytokines, including IL-6, IL-1β, TNF-α, IL-8, IL-2, IL-17, G-CSF, GM-CSF, CXCL10, CCL2, CCL3 in patients with COVID-19 [14]. These cytokines can also cause extensive pulmonary damage through the accumulation of neutrophils and macrophages in lung tissue, leading to the development of hyaline membranes and diffuse thickening of the alveolar barrier and ultimately diffuse alveolar damage [72].…”
Section: Role Of Il-6 In Tissue Damagementioning
confidence: 99%
See 1 more Smart Citation
“…All evidence suggests a possible destructive role for IL-6 in patients with SARS-COV-2 infection [71]. Shock and organ failure in several organs, such as the kidneys, heart, lungs, and liver, are severely damaged by cytokine storms caused by an increase in inflammatory cytokines, including IL-6, IL-1β, TNF-α, IL-8, IL-2, IL-17, G-CSF, GM-CSF, CXCL10, CCL2, CCL3 in patients with COVID-19 [14]. These cytokines can also cause extensive pulmonary damage through the accumulation of neutrophils and macrophages in lung tissue, leading to the development of hyaline membranes and diffuse thickening of the alveolar barrier and ultimately diffuse alveolar damage [72].…”
Section: Role Of Il-6 In Tissue Damagementioning
confidence: 99%
“…However, there is no accurate information on how other immune cells, such as T-cells, a type of lymphocytes, and DCs, are infected. Following SARS-CoV-2 infection, dysregulated inflammatory responses, infiltration of neutrophils, monocytes, and macrophages, as well as uncontrolled release of inflammatory cytokines and chemokines are taken into account as critical factors in the development of severe pneumonia, acute respiratory distress syndrome (ARDS), or MOF [11][12][13][14]. Several studies have correspondingly demonstrated a significant increase in IL-6 serum levels in patients suffering from COVID-19 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, these problems may become chronic 7 . Our observations that a past history of a chemical war injury does not add to the risk of COVID-19 and does not modify its clinical picture are intriguing and should be replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylcysteine has also recently been proposed as both a preventative and therapeutic agent against COVID-19 due to its abilities to reduce the excessive mucus production, GSH depletion, oxidative stress and inflammation in the lungs that this virus causes [ [122] , [123] , [124] , [125] , [126] , [127] ], and several clinical trials are being carried out to assess NAC’s efficacy against this disease [ [128] , [129] , [130] , [131] ]. Interestingly, it has also been noted “that there are some similarities in the pathogenesis of SARS-CoV-2 and mustard gas in immune system disruption and pulmonary infection” [ 132 ], including up-regulation of lung angiotensin-converting enzyme (ACE2), the receptor for SARS-CoV-2. The authors speculate that these commonalities will lead to increased susceptibility and more severe outcomes in Iranian survivors of H exposure to COVID-19 [ 132 ].…”
Section: Nac In Other Clinical Applications and Safetymentioning
confidence: 99%
“…Interestingly, it has also been noted “that there are some similarities in the pathogenesis of SARS-CoV-2 and mustard gas in immune system disruption and pulmonary infection” [ 132 ], including up-regulation of lung angiotensin-converting enzyme (ACE2), the receptor for SARS-CoV-2. The authors speculate that these commonalities will lead to increased susceptibility and more severe outcomes in Iranian survivors of H exposure to COVID-19 [ 132 ].…”
Section: Nac In Other Clinical Applications and Safetymentioning
confidence: 99%